PENGARUH BERKUMUR KLORHEKSIDIN 0,1% DAN XYLITOL TERHADAP PERTUMBUHAN PLAK PADA PENGGUNA ORTODONTI CEKAT - Raden Aditya Wisnu Wardhana; Dwi Leni Yuliana (Universitas Muhammadiyah Semarang, 2023)
Background: Fixed orthodontic is one of the orthodontic treatments that cannot be removed by the patient because they are attached directly to the teeth using an adhesive material. The complex shape of fixed orthodontic components makes it difficult to clean so that bacteria will multiply and form plaque. In addition to brushing teeth, Plaque control in fixed orthodontic users needs to be supplemented with mouthwash. Gargling 0.1% chlorhexidine solution and xylitol solution is one of the many ways to achieve good plaque control. Research purpose: To determine the difference in the effect of gargling with 0.1% chlorhexidine solution and xylitol solution on plaque growth in fixed orthodontic users. Method: The type of this study is clinical experimental research with one group pretest posttest design approach. The number of participants are 30 people, treated with gargling 0.1% chlorhexidine solution and xylitol solution. The plaque index was examined before and after gargling with 0.1% chlorhexidine solution and xylitol solution for fixed orthodontic patient.Result: there was a significant decrease in plaque index before and after gargling with 0.1% chlorhexidine solution and xylitol solution. Independent-t test (p<0.05) showed that there was no significant difference between the difference in plaque index reduction in the group that gargled with 0.1% chlorhexidine solution and the group that gargled with xylitol solution.Conclusion: Gargling with 0.1% chlorhexidine solution is more effective in reducing plaque index than gargling with xylitol solution although there was no significant difference.